The coronavirus pandemic in a crooked mirror of the Polish newspaper joke - Sikorska-Bujnowicz, Katarzyna (Acta Universitatis Lodziensis. Folia Germanica, 2023)
The analysis of the “Tygodniówka” column published on the last page of a weekly magazine “Angora” for the years 2020–2021 made it possible to evaluate the way of presenting an individual and his everyday life during the COVID-19 pandemic in a crooked mirror of cartoon jokes. During one year there is an evident change in attitudes and behaviour of people who have already got used to the pandemic to some extent. Due to the length of the material collected and the most visible change that took place in the way of presenting the mocked events, attitudes and human behaviour in the past year, two specific issues of “Angora” were selected, i.e. 49/2020 and 49/2021. In addition, the examples from the holiday issue 33/2021 have shown how the behaviour of an individual living in constant fear of the coronavirus changes during a vacation. A man tired of the prohibitions and sanitary regime to be in force also seeks opportunities not to follow them for a while. He consciously circumvents restrictions and prohibitions, does not comply with the sanitary regime, which is manifested by the resignation from wearing masks and maintaining social distance. All of this can be found in the jokes of “Tygodniówka”, where mercilessly accurately reflects the pandemic reality, although it’s been showed in the crooked mirror. The person seems to be sure that the coronavirus has magically ceased to be a threat, perhaps even disappeared.